Принципы стратегического управления проектами, программами и портфелями медицинского учреждения - Данченко, Елена Борисовна; Лепский, Владлен Владимирович (НТУ "ХПИ", 2017)
В статье проведен краткий обзор результатов последних научных исследований в направлении применения проектного подхода к управлению медицинскими учреждениями. Предложена концепция интегрированного управления медицинскими учреждениями, которая включает одновременно стратегический, проектный, портфельный, программный подход к управлению (С3П-концепция). Впервые сформулированы парные принципы С3П-управления. Данная концепция и предложенные принципы интегрированного управления являются универсальными и могут быть применены в любой проектно-ориентированной предметной области.

The article gives a brief overview of the latest research in the direction of the use of project-based approach to the management of medical institutions. It is shown that medicine today is a project-oriented area, and modern scientific studies suggest the use of not only the project management approach, and portfolio management. The various scientific sources proposed classification of projects of medical institutions, mechanisms of formation of projects portfolios of such institutions. The concept of integrated management of medical institutions, which includes strategic, project, portfolio, program management approach (S3P-concept), is offered. According to this concept, the process of S3P-management of medical institution will include four stages, which are closely interrelated. For the first time the pair principles of S3P-management are formulated. The proposed concept and principles of S3P-management of medical institution require further development and creating of models, methods and integrated management tools, as well as the development of a system of indicators verify compliance with the organization's strategy of its projects, projects portfolios and programs. This concept and the proposed integrated management principles are universal and can be applied to any project-oriented area.
Strategic project management principles, programs and portfolios of the medical institution
Keywords: проект; программа; портфель проектов; медицинские учреждения; концепция; стратегическое управление; принципы; project; program; portfolio of projects; medical institutions; concept; strategic management; principles